Utilization of Kelotok as a Means of River Tourism Transportation in Siring Tendean Banjarmasin - Auliya, Desy; Rusmaniah, Rusmaniah; Jumriani, Jumriani; Syarifuddin, Syarifuddin; Nur'aini, Fatwa (Program Studi Pendidikan IPS, 2026)
The use of kelotok in the Siring Tendean Banjarmasin area reflects a shift in function from traditional transportation to an important part of the cultural tourism ecosystem. The purpose of this study is to analyze the use of kelotok as a learning resource in river tourism transportation in the Siring Tendean Banjarmasin area and to identify tourism activities that can be undertaken using kelotok. This research method uses qualitative research methods to analyze the use of kelotok as a learning resource in river tourism transportation in the Siring Tendean Banjarmasin area and to identify tourism activities that can be undertaken using kelotok. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used data reduction based on the research objectives, data presentation based on descriptions, and data conclusions based on the drawing of conclusions. Data validity testing was carried out using triangulation techniques. The management of kelotok carried out independently by the association reflects the high level of community participation in tourism development. The conclusion is that kelotok tourism is able to support the local economy while strengthening the identity of river culture as a sustainable tourist attraction in Banjarmasin City.